2014
DOI: 10.1002/jmri.24761
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging of prostate cancer using a statistical model based on the gamma distribution

Abstract: A statistical model based on the gamma distribution proved suitable for describing diffusion signal decay curves of PCa. This approach may provide better correlation between diffusion signal decay and histological information in the prostate gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Oshio et al reported a higher f 1 fraction for prostate cancer relative to the normal peripheral zone. In the Shinmoto et al study, a significantly higher f 1 fraction was reported in prostate cancer relative to benign prostatic hyperplasia as in the actual study comparing benign and malignant breast lesions. In the same study, a higher f 3 fraction was reported in benign prostatic hyperplasia relative to prostate cancer and that was also found in the present study comparing benign and malignant breast lesions.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Oshio et al reported a higher f 1 fraction for prostate cancer relative to the normal peripheral zone. In the Shinmoto et al study, a significantly higher f 1 fraction was reported in prostate cancer relative to benign prostatic hyperplasia as in the actual study comparing benign and malignant breast lesions. In the same study, a higher f 3 fraction was reported in benign prostatic hyperplasia relative to prostate cancer and that was also found in the present study comparing benign and malignant breast lesions.…”
Section: Discussionmentioning
confidence: 79%
“…Another approach is the application of the gamma function to the statistical distribution of ADC values: the gamma distribution (GD) model . This model is expected to reflect the probability of the distribution of water molecule mobility in different regions of the tissue .…”
mentioning
confidence: 99%
See 3 more Smart Citations